2021
DOI: 10.3390/brainsci11040421
|View full text |Cite
|
Sign up to set email alerts
|

Lights Out: Examining Sleep in Children with Vision Impairment

Abstract: Sleep is crucial for development across cognitive, physical, and social-emotional domains. Sleep quality and quantity impact domains of daytime functioning, attainment, and global development. Previous work has explored sleep profiles in typically developing children and children with developmental disorders such as Down syndrome and Williams Syndrome, yet there is a complete absence of published work regarding the sleep profiles of children with vision impairment aged 4–11 years. This is the first known study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
(56 reference statements)
1
1
0
Order By: Relevance
“…Generally, our exploratory findings are consistent with the previous literature that reports greater sleep disturbance in children with a developmental disability (e.g., [7,8,76]), including autism (e.g., [77][78][79]) in relation to typically developing peers, and contradicted previous findings [27] where developmental condition (i.e., VI or typically developing) did not predict poor sleep outcomes. The CSHQ results further provide evidence that the comorbidity of VI + autism might be a stronger driving condition behind sleep problems and sleep disturbance in the pediatric population compared to a diagnosis of VI or autism alone.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Generally, our exploratory findings are consistent with the previous literature that reports greater sleep disturbance in children with a developmental disability (e.g., [7,8,76]), including autism (e.g., [77][78][79]) in relation to typically developing peers, and contradicted previous findings [27] where developmental condition (i.e., VI or typically developing) did not predict poor sleep outcomes. The CSHQ results further provide evidence that the comorbidity of VI + autism might be a stronger driving condition behind sleep problems and sleep disturbance in the pediatric population compared to a diagnosis of VI or autism alone.…”
Section: Discussionsupporting
confidence: 87%
“…Adults with vision impairment have predominantly been the focus of the literature to date [23][24][25][26]. Hayton et al [27] reported that both typically developing children and children with vision impairment (VI; ranging from blindness to partial sight) had poor sleep quality and suboptimal sleep quantity on specific measures of sleep, indicating that sleeping problems were characteristic of the pediatric population, and not specific to diagnosis. However, the sample in [27]'s study did not extend to children with dual diagnoses of vision impairment and autism, nor any other comorbid condition.…”
Section: Introductionmentioning
confidence: 99%